Basic principles for the design of cutting edge roundings. Issue 1 (2018) - Bergmann, Benjamin; Grove, Thilo
Abstract: Adapted cutting edge roundings lead to a performance increase of cutting tools. The optimal cutting edge design is determined by the thermomechanical process load and thus depends on the machined material. In this study, the external mechanical load is investigated in direct relation to material properties by means of microcinematography. It could be shown that load characteristics are mainly material independent, whereas the load level depends on the machined material. Finally, the findings were transferred into a model, which enables the design of cutting edge roundings based on material properties.